The crystal-chemistry of riebeckite, ideally Na2Fe32+ Fe23+Si8O22(OH)2: a multi-technique study. (28th August 2018) - Susta, Umberto; Della Ventura, Giancarlo; Hawthorne, Frank C.; Abdu, Yassir A.; Day, Maxwell C.; Mihailova, Boriana; Oberti, Roberta
Abstract: In this work we report on a complete crystal-chemical characterization of a near end-member riebeckite from Malawi, and use the available data to critically compare information obtained from different analytical methods. The sample occurs as well-formed and very large single crystals in pegmatitic rocks. Accurate site-populations were determined by combining single-crystal structure refinement and electron microprobe analysis (EMPA). The Fe 3+ /Fe 2+ ratio was obtained from Mössbauer spectroscopy. Lithium was quantified by Laser Ablation Inductively Coupled Plasma Mass Spectroscopy (LA-ICP-MS). Fourier-Transform Infrared (FTIR) spectra, collected both on powders and single crystals, are presented and discussed. FTIR spectra in the NIR region are also presented for the first time for this amphibole. The FTIR data are compatible with complete local ordering of A cations close to F, and complete Fe 2+ /Mg disorder at M (1, 3). Polarized Raman-scattering data collected from single crystals confirm this conclusion. In addition, it was found that FTIR data collected on powders provide the best agreement with the site occupancies derived from chemical (EMPA and LA-ICP-MS) and crystal-chemical data, possibly because they do not depend on experimental issues such as orientation and polarization.